Dynamic Changes of Th1 Cytokines and the Clinical Significance of the IFN-γ/TNF-α Ratio in Acute Brucellosis - Guang Xu; Peng Zhang; Rongjing Dang; Yanfang Jiang; Feng Wang; Bin Wang; Mingyuan Yang (Mediators of Inflammation)
Background. T-helper type 1 (Th1) cells and Th1-produced cytokines play essential roles in the immune response to foreign pathogens, such as Brucella spp. The aim of this study was to evaluate the dynamic changes of Th1 cells and Th1-produced cytokines in patients with acute brucellosis and their impact on clinical decision-making. Methods. Fifty-one individuals with acute brucellosis and 17 healthy subjects were enrolled in this study. The brucellosis patients were diagnosed based on clinical symptoms, laboratory tests, and clinical examination. The levels of serum gamma-interferon (IFN-γ) and tumor necrosis factor-alpha (TNF-α), along with the percentage of Th1 cells, were determined by flow cytometry bead arrays (CBA). Results. The frequency of Th1 cells, along with the levels of IFN-γ and TNF-α, was negatively correlated with the clinical parameters. The mean serum levels of IFN-γ and TNF-α and the frequency of Th1 cells were significantly higher in the brucellosis patients in comparison with the healthy subjects (p<0.05). Besides, the cytokine levels were not significantly different between the positive and negative blood culture groups. IFN-γ levels significantly decreased from 6 months to 12 months post treatment (p<0.05). However, the IFN-γ levels remained higher than those of the healthy subjects by 12 months post treatment (p<0.05). The IFN-γ/TNF-α ratio was significantly higher in severe cases than in nonsevere cases (p<0.05). Conclusions. The IFN-γ levels secreted by Th1 cells remain significantly higher than those of healthy subjects more than 12 months after treatment with antibiotics. This finding is different from similar studies. The IFN-γ/TNF-α ratio may be a feasible parameter for assessing clinical severity, yet further longitudinal studies of the immunization and inflammatory reaction of brucellosis are needed in larger patient populations.